The Influence of Diabetes Self-Management Education on Increasing Knowledge, Self-Management, and Current Blood Sugar Level Control in Type 2 Diabetes Mellitus Patients - Hana Zumaedza Ulfa; Yani Sofiani; Ninik Yunitri; Fitrian Rayasari; Wati Jumaiyah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type 2 diabetes mellitus (DM type 2) is a serious problem worldwide due to the impact of the disease which can cause complications and reduce the quality of life of sufferers. Factors that cause this are due to lack of knowledge, self-management and chronic hyperglycemia. Therefore, it is necessary to carry out continuous educational interventions such as Diabetes Self-Management Education (DSME). The purpose of this implementation is to improve knowledge, self-management and control of random blood sugar levels in patients with type 2 DM. This type of quantitative research uses a one-group pre-test-post-test approach, a sample of 15 respondents and the sampling technique used was purposive sampling. The implementation time is April 21 to May 24, 2025 at Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province. The measurement instruments used are Diabetes Knowledge Questionnaire (DKQ-24), Diabetes Self-Management Instrument (DSMI) and GDS measurement sheets. The analysis used is the paired t-test and the Wilcoxon test. The results of the implementation after being given 4 sessions of DSME showed an increase in knowledge as shown by a p-value of 0.003 (<0.05), an increase in self-management with a p-value of 0.001 (<0.05) and control of random blood glucose values with a p-value of 0.001 (<0.05).0.000 (<0.05). The 4-session ideo-based DSME had a positive impact on knowledge, self-management, and random blood sugar values because DSME is a continuous educational intervention that helps respondents understand their disease better.